Identification of Races 0 and 2 of Cladosporium fulvum (syn Passalora fulva) on Tomato in the Cinturón Hortícola de La Plata, Argentina - Rollán, María Cristina (2013)
Surveys aimed at evaluating the incidence and severity of a new disease that developed in greenhouses cultivated with tomato (Solanum lycopersicum L.) were performed during 2009 and 2010 in greenhouses of the cultivars Elpida (Enza Zaden) and Colibrí (Clause) in an area of tomato production known as the Cinturón Hortícola de La Plata (the “horticultural belt of La Plata”). The disease had a 100% prevalence and 90% incidence within the ten 250 m greenhouses that were monitored in 2009, 2010, and 2011. In two consecutive assays, severity was 40%. The wide distribution of the disease suggests that the tomato hybrids under use lack resistance genes.